TECHNOLOGIES FOR SYSTEMATIZING THE RESEARCH ACTIVITIES OF FUTURE TEACHERS IN THE PROCESS OF EDUCATIONAL INTEGRATION (Multidisciplinary Journal of Science and Technology, 2025)
This article studies the technologies of systematization of research activities of future teachers in the process of educational integration. The study analyzed the effectiveness of project-based learning, integrated lessons, e-learning platforms and mentoring systems. Based on the results of experimental work, questionnaires and monitoring, it was confirmed that the technologies of systematization of research activities according to the principles of educational integration are of great importance in increasing the scientific potential of future teachers, improving independent thinking and professional training. The difficulties that arise in the use of new technologies and ways to overcome them were also considered. The article can be a useful resource for educators and researchers interested in the innovative development of the educational process.